Job Market Stars - Abel Brodeur; Lamis Kattan; Marco Musumeci (Global Labor Organization (GLO), 2024)
Graduating economics PhDs face intense competition when seeking faculty or research positions at universities and research institutions. We examine the relationship between statistically significant results, arguably used as indicators of research quality in a competitive academic market, and academic hiring outcomes. We start by investigating the determinants of academic success by analyzing 604 job market papers (JMPs) from 2018-2019 to 2020- 2021. We then turn to the importance of statistical significance focusing on 150 empirical JMPs. We find evidence that 'marginally' significant results in JMPs are associated with higher academic placement likelihoods. During the COVID-19 pandemic, a tighter job market strengthened this relationship without altering the p-hacking behavior of PhD candidates, suggesting that our results reflect a recruitment bias by academic employers. We also find evidence of publication bias, suggesting that recruiters may use statistical significance to gauge candidates' potential for future publications, thus influencing recruitment decisions. Overall, our findings provide insights into the dynamics of the academic job market and highlight incentives that would potentially reward academics for questionable research practices.
Keywords: B41; C13; C40; C93; 330; Academic job market; p-Hacking: Publication bias; Research credibility